How Entrepreneurship Education and Demographic Factors Shape Entrepreneurial Intention: The Mediating Role of Entrepreneurial Attitude - Gerry Gregorius; Rahcmad Budi Suharto; Jiuhardi Jiuhardi; Djoko Setyadi (Universitas Negeri Makassar, 2025)
In recent years, unemployment among university graduates has remained an important economic challenge, increasing the relevance of entrepreneurship as a strategic pathway for employment creation and economic resilience. This study examines the direct and indirect effects of entrepreneurship education and demographic factors on entrepreneurial intention, with entrepreneurial attitude serving as a mediating variable. A quantitative explanatory approach was employed to investigate the relationships among the proposed variables. Data were collected from 78 respondents selected through proportional random sampling in a higher education context. The findings indicate that entrepreneurship education, demographic factors, and entrepreneurial attitude significantly influence entrepreneurial intention, both directly and indirectly. The results further suggest that entrepreneurial attitude functions as an important mediating mechanism that strengthens the contribution of entrepreneurship education and demographic characteristics to entrepreneurial intention. These findings imply that strengthening entrepreneurial intention requires not only effective entrepreneurship education but also greater attention to individual background characteristics and the formation of positive attitudes toward entrepreneurship. This study offers practical implications for higher education institutions in designing entrepreneurship learning programs that are more adaptive, inclusive, and oriented toward the development of entrepreneurial mindset and intention. The study also provides a basis for future research to expand the model by incorporating additional predictors and broader methodological approaches.